Phylloporus pruinatus, a new lamellate bolete from subtropical China - Zhao, Kuan; Zeng, Nian-Kai; Han, Li-Hong; Gao, Xiao-Ye; Liu, Jian-Tao; Wang, Song-Hua; Gu, Bing (Phytotaxa, 2018)
Phylloporus pruinatus is described as a new species characterized by its small basidiomata about 2–3 cm diam, a yellowish brown to reddish brown pileal surface covered with a thin white pruina, white to cream yellow context, whitish basal mycelium and small spores. Molecular phylogenetic analyses based on three gene makers (ITS, nrLSU and tef1-α) also confirmed it belongs to the genus Phylloporus and that it is distinct from any known species. Morphological illustrations and descriptions are provided.